2017
DOI: 10.1159/000456532
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the AN69ST Membrane versus Citrate-Enriched Dialysate on Clotting Events during Hemodialysis without Systemic Anticoagulation

Abstract: Background: The optimal management of anticoagulation in hemodialyzed patients with a high risk of bleeding is controversial. Methods: We compared premature termination of dialysis caused by clotting events between AN69ST membranes (G1) and 0.8 mmol/L citrate-enriched dialysate (G2). The number of sessions that had increased venous pressure (VP) and variations in urea-reduction ratio (URR) were analyzed. Results: Six hundred and two sessions were analyzed in 259 patients: 22.4% had sessions that ended prematur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This likely would not have influenced the results since (i) the same dialysate was used for both modalities and (ii) certain other studies have demonstrated that citrate-containing dialysate does not significantly reduce clotting in the extracorporeal circuit. [20][21][22] In addition to the clotting issue, predilution HDF may provide some benefit over HD by increasing the clearance of the middle molecules; however, the convective flux in our study was probably not sufficiently high to achieve a significant effect and, moreover, the positive effect of increased clearance may be blunted by the premature clotting. As shown by the ionic dialysance, the diffusive epuration of the small solutes was comparable between the two techniques.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This likely would not have influenced the results since (i) the same dialysate was used for both modalities and (ii) certain other studies have demonstrated that citrate-containing dialysate does not significantly reduce clotting in the extracorporeal circuit. [20][21][22] In addition to the clotting issue, predilution HDF may provide some benefit over HD by increasing the clearance of the middle molecules; however, the convective flux in our study was probably not sufficiently high to achieve a significant effect and, moreover, the positive effect of increased clearance may be blunted by the premature clotting. As shown by the ionic dialysance, the diffusive epuration of the small solutes was comparable between the two techniques.…”
Section: Discussionmentioning
confidence: 60%
“…In the present study, we used a dialysate containing citrate at very low concentration. This likely would not have influenced the results since (i) the same dialysate was used for both modalities and (ii) certain other studies have demonstrated that citrate‐containing dialysate does not significantly reduce clotting in the extracorporeal circuit …”
Section: Discussionmentioning
confidence: 99%
“…125,126 The comparison between AN69ST membrane and citrate-enriched dialysate did not assess differences on clotting events and dialysis session premature suspension, in patients at high risk of bleeding. 127 However, a retrospective analysis of 309 HD sessions, performed without systemic anticoagulation, due to high risk of bleeding, with a contemporary use of heparin-…”
Section: Anti Coag Ul Ati On Sys Temmentioning
confidence: 99%
“…However, when compared to regional citrate coagulation, the heparinized filter was less efficient, in terms of clotting of the extracorporeal circuit and dialysis efficacy, as revealed by a prospective and controlled trial in which heparin‐grafted polyacrylonitrile (AN69ST) dialyzer, in the absence of systemic anticoagulation, was complicated by high incidence of circuit coagulation 125,126 . The comparison between AN69ST membrane and citrate‐enriched dialysate did not assess differences on clotting events and dialysis session premature suspension, in patients at high risk of bleeding 127 . However, a retrospective analysis of 309 HD sessions, performed without systemic anticoagulation, due to high risk of bleeding, with a contemporary use of heparin‐grafted AN69ST dialyzer membrane and citrate‐enriched dialysate, demonstrated successful data, with completed sessions for treatment times of ≥4 hours achieved in 81% of patients 128 …”
Section: Anticoagulation Systemmentioning
confidence: 99%
“…In China, there are three common anticoagulation means clinically, including unfractionated heparin (UFH), low-molecular-weight heparin (LMWH), and 'no heparin,' where LMWH is the prioritized option in maintenance HD. However, CKD patients already have an increased risk of excess bleeding, such as platelet dysfunction caused by uremia (2,3), let alone the potentially fatal heparin-induced thrombocytopenia type II and 'no heparin'-induced consumption of platelet when receiving dialysis (4,5). Regional citrate anticoagulation has been tested on dialysis, but it might lead to potentially disastrous complications, such as citrate accumulation presenting metabolic acidosis, hypernatremia, and citrate net overload presenting metabolic alkalosis (6).…”
Section: Introductionmentioning
confidence: 99%